(De)politicization of COVID-19 Pandemic in the Implementation of 2020 Simultaneous Regional Elections - Yuseptia Angretnowati; Palupi Anggraheni (Institut Teknologi Sepuluh Nopember, 2021)
Coronavirus disease (COVID-19) takes effect on state management in Indonesia. Good crisis management is necessary to mitigate COVID-19. This research uses Beland ‘s conceptual framework on politics of insecurity and its implementation on the state's management crisis process, especially on how the state protects its citizens towards non-traditional threads while performing political accountability. The 2020 Simultaneous Regional Election (Pilkada) during pandemic is positioned as a case study, especially on how policy conflicts and calculation of benefits-risks occur. It has a pivotal role in establishing perception of collective thread. In the case of 2020 Simultaneous Regional Election, conflict in policy creates social anxiety and political tension caused by a health crisis. This research finds that the government (de) politicized the 2020 Simultaneous Regional Elections by using a repertoire of types of strategies, i.e. avoiding blame and claiming credit, which were carefully compiled and implemented in a specific frame.